Serological point-of-care and label-free capacitive diagnosis of dengue virus infection - Cecchetto, Juliana [UNESP]; Santos, Adriano [UNESP]; Mondini, Adriano [UNESP]; Cilli, Eduardo M. [UNESP]; Bueno, Paulo R. [UNESP] (Elsevier, 2020)
Dengue non-structural protein 1 (NS1 DENV) is considered a biomarker for dengue fever in an early stage. A sensitive and rapid assay for distinguishing positive from negative dengue infection samples is imperative for epidemic control and public health in tropical regions because it enables the development of instantaneous updatable databases and effective surveillance systems. Presently, we successfully report, for the first time, the use of the electrochemical capacitive method for the detection of NS1 DENV biomarker in human serum samples. By using a ferrocene-tagged peptide modified surface containing anti-NS1 as the receptor, it was possible to differentiate positive from negative samples with a p < 0.01 in a reagentless and label-free capacitive format. This capacitive assay had a cut-off of 1.36% (confidence interval of 99.99%); it therefore opens new avenues for developing miniature label-free electrochemical devices for infectious diseases.
Keywords: Capacitive biosensors; Electrochemical capacitance; Electrochemical impedance spectroscopy; Label-free diagnostics; Molecular assaying; Point-of-care diagnostics